Nemški prevodi Lipuševih del ob in po Tjažu v luči konsekracije - Kohl, Felix Oliver (Primerjalna književnost, 2018)
The article deals with the role of the translator in consecrating the works of Florjan Lipuš in the germanophone literary public sphere. The translation of his novel Zmote dijaka Tjaža into German by Peter Handke and Helga Mračnikar in 1981 marked a milestone both for Lipuš's career as a writer and the Carinthian-Slovene literature in general. Handke transferred his symbolic capital, which he gained as a successful writer, onto both and helped them to a wider recognition among the germanophone literary public. After this, Handke handed the role of Lipuš's translator over to Fabjan Hafner (until 1997), who was then followed by Johann Strutz. For both, translating Lipuš served as a stepping-stone to successful careers as translators with both receiving positive criticisms all over and, in addition, several awards for their work. However, they themselves have no significant consecration power as their work has been overlooked on many occasions. Their translations are highly estimated by literary scholars and connoisseurs of Austrian literature, but they have not achieved significant recognition in the broader field of germanophone literary public sphere. This of course correlates with Lipuš's career itself, who, after the storm that had aroused around Handke's translation calmed down, remained a "sleeper" for almost 30 years, until Handke came into play again. In 2011 he promoted Strutz's translation of Boštjanov let (2005) in different ways, which vaulted Lipuš back into the centre of media attention. By this, Handke once again proved to be the driving force in the promotional network of Lipuš's literature, which can be seen also in germanophone media: While writing about Lipuš they frequently tend to pay special attention to Handke's name and at the same time often conceal the achievements of Lipuš's actual translators.
Keywords: Handke, Peter; Lipuš, Florjan; literarno prevajanje; prevodi v nemščino; slovenska književnost